Teacher Professional Ethics: Moral Foundations and Professionalism in Islamic Education - Rahman, Abdul; Aprison, Wedra; Dina, Hidayatul; Harto, Budi; Susanti, Riri (STIT Ahlussunnah Bukittinggi, 2025)
This article examines the professional ethics of teachers, which form the moral and professional foundation for carrying out their duties as educators in Islam. The purpose of this study is to analyze the ethical values inherent in the teaching profession and their relevance in shaping character and the quality of Islamic education. This research uses a qualitative method based on literature study by examining classical and contemporary literature related to the concept of teachers in Islam. The results show that the professional ethics of teachers are an integral part of teaching duties, requiring teachers to always act fairly, honestly, trustworthily, and uphold noble moral values in all educational interactions. The essence of teachers in Islam includes the terms murabbi, mu'allim, and mu'addib. Teacher professionalism in Islamic education is seen in the Qur'an, among others, that teachers must be trustworthy, have integrity and honesty, and be able to be role models for students. The implications of this study emphasize that strengthening the professional ethics of teachers is not only important for improving the quality of Islamic education, but also serves as a foundation for building a generation with character, noble morals, and readiness to face the challenges of the times. This article discusses the professional ethics of teachers in Islamic education.